Performance Analysis Bank Group Based on Core Capital 4 (KBMI4) 2017–2022 - Santosa, Bernadus Dwi Joko; Efni, Yulia; Indrawati, Novita (InJEBA : International Journal of Economics, Business and Accounting, 2024)
In this research, a sample of banks from the KBMI 4 group is used to describe banking sustainability during the COVID-19 crisis. In this group, bank profits and assets increased during the event period. The aim of this research is to see and analyze the influence of six (six) independent variables on bank profit achievement. Apart from that, this research also evaluates and analyzes the influence of the type of ownership and the time period of the incident on the achievement of bank profits, to determine which entity is most effective in achieving bank profits at this time. In this research, multiple regression methods and difference tests were used. The results show that three variables (ASSET, BOPO, and LDR) have an impact on profits, while three variables (CAR, NPL, and NIM) have no influence. However, based on the type of bank ownership between State-Owned Enterprises and National Private Enterprises or based on the time period of the incident, there is no difference in influence in achieving bank profits.